Pengembangan Case Manager Dalam Patient Centered Care - Wiwin Nur Aeni (Jurnal Manajemen Keperawatan, 2014)
The treatment process of the patient is a complex process because it involves sharing of health professions from nurses, doctors, pharmacists, nutrition, as well as administrative personnel. Constraints that occur in the field is the communication between the health team did not fully running. Effective communication between the teams is a necessary condition to provide nursing services primarily focused to patients. Patient centered care is care that is respectful and responsive to choices, needs and personal values of patients and ensuring that value as a guide for all clinical decisions. The aim of this systematic review is to analysis of the development of case manager towards the fulfillment of the rights of patients. Methods : This study used critical appraisal method by leveling the evidence based nursing from proceeding, thesis, dissertation, national as well as international journals. Results : Case manager can meet patients' rights through effective communication. Case manager works closely with the patient so that the maintenance time nurse to the patient lasts a long time since the patient came to the patient's home. Case manager through its role in collecting and organizing various data related to the patient and treatment process which traces the disease, needs, and the potential that exists in the patient so that reconcile the needs / expectations and patient compliance. Conclusions : The effectiveness of case manager in the fulfillment of patients' rights need to be developed early on in the hospital.